Design and Development of a Multi-channel Wireless Data Logger for Energy Measurement - Ab Halim, Nurul Azura; Roziah Aziz (Evolution in Electrical and Electronic Engineering, 2023)
Electricity consumption rises year after year, particularly during the COVID-19 pandemic where more individuals are expected to work from home. It will have an impact on the electricity bill. Consumers must reduce their electrical usage to reduce their electric costs in the home sector. The main predicament is that they do not know what equipment or activities consume more power than other outlets, or which outlet is less efficient even though the electrical equipment at that outlet does not require high power. Thus, the measurement tool for home power monitoring of electrical outlets was conceived and prototype utilizing ESP32 Wi-Fi module for wireless communication. The monitoring result can be seen via LCD which provides voltage, current and real power readings. The adoption of this prototype makes it easy for the residential electricity sector to determine which outlet uses the most power compared to the others.